Practices Regarding Human Papillomavirus and Cervical Cancer in A Sample of Paramedical Staff in Al- Najaf Governorate, Iraq - Salih, Alaa Mehdi; Al –Sarray, Atta Ah Mousa (Journal of Techniques, 2022)
The papillomaviridae viral family includes HPV. When it comes to female sexually transmitted diseases, the genital tract is the primary site of infection for genital type HPVs, which are further divided into high- and low-risk subgroups depending on the likelihood that they will cause cancer of the genital tract. High-risk HPV strains 16 and 18 cause cervical cancer. Sexual contact or skin-to-skin contact is the primary mode of transmission of HPV. To assess the degree of Practice among a sample of paramedical workers concerning the Human Papillomavirus and Cervical Cancer. Five hospitals and 25 primary health care centers in the Al-Najaf governorate were studied in this cross-sectional observational descriptive cross-sectional research. Starting on December 19th, 2021 and concluding on April 18th, 2022, data was gathered for four months. According to the results of the present research, which included (five hundred) Paramedical employees aged 20-59 years, the age group with the largest proportion (66.4%) was that of 20-29 years. Whereas, in terms of gender, the largest proportion of women (64.6 percent). Almost all paramedics work in urban areas. In addition, almost half of the participants came from medical institutions, accounting for 51.6 percent of the total, while just 2.4 percent were graduates of secondary schools. Only 2.4% of the paramedical staff had any kind of education or training on HPV or cervical cancer. Excellent practice evaluations for the Human Papillomavirus and cervical cancer were much higher among paramedical providers (79 percent). Most of the paramedics who were evaluated for their practices addressing cervical cancer and the human papillomavirus (HPV) received good grades. Health authorities, social groupings, and non-governmental organizations should work together to communicate information about the human papillomavirus and cervical cancer to the general population. In order to educate and sensitize medical professionals about HPV screening technologies and the most current screening and treatment guidelines, conduct educational initiatives.